Free carrier enhanced depletion in ZnO nanorods decorated with bimetallic AuPt nanoclusters. Issue 37 (14th September 2020) - Bahariqushchi, R.; Cosentino, S.; Scuderi, M.; Dumons, E.; Tran-Huu-Hue, L. P.; Strano, V.; Grandjean, D.; Lievens, P.; Poulin-Vittrant, G.; Spinella, C.; Terrasi, A.; Franzò, G.; et al.
Abstract : AuPt nanocluster decoration of ZnO nanorods augments dark resistance (500×) and UV light sensitivity (10×) much more than Au or Pt decoration. Abstract : The decoration of semiconductor nanostructures with small metallic clusters usually leads to an improvement of their properties in sensing or catalysis. Bimetallic cluster decoration typically is claimed to be even more effective. Here, we report a detailed investigation of the effects of Au, Pt or AuPt nanocluster decoration of ZnO nanorods on charge transport, photoluminescence and UV sensitivity. ZnO nanorods were synthesized by chemical bath deposition while decoration with small nanoclusters (2–3 nm in size) was achieved by a laser-ablation based cluster beam deposition technology. The structural properties were investigated by scanning electron microscopy, high resolution transmission electron microscopy, X-ray photoelectron spectroscopy and Rutherford backscattering spectrometry, and the optoelectronic properties by current–voltage and photoluminescence measurements. The extent of band bending at the cluster–ZnO interface was quantitatively modeled through numerical simulations. The decoration of ZnO nanorods with monometallic Au or Pt nanoclusters causes a significant depletion of free electrons below the surface, leading to a reduction of UV photoluminescence, an increase of ZnO nanorod dark resistance (up to 200 times) and, as a consequence, an improved sensitivity (up to 6 times) to UV light. These effects are strongly enhanced (up to 450 and 10 times, respectively) when ZnO nanorods are decorated with bimetallic AuPt nanoclusters that substantially augment the depletion of free carriers likely due to a more efficient absorption of the gas molecules on the surface of the bimetallic AuPt nanoclusters than on that of their monometallic counterparts. The depletion of free carriers in cluster decorated ZnO nanorods is quantitatively investigated and modelled, allowing the application of these composite materials in UV sensing and light induced catalysis.